La crisi e le riforme del mercato del lavoro in Italia: un’analisi regionale del Jobs Act - Guarascio, Dario; Fana, Marta; Cirillo, Valeria (Argomenti, 2017)
This paper provides an analysis of the dynamics of the Italian labor market after the introduction of the Jobs Act analyzing, in particular, the regional dimension. In line with the evidence shown in Fana et al. (2016), we show that, after the Jobs Act, temporary employment increased more than permanent one. Moreover, it emerges as the slight increase in employment is significantly linked to the stabilization of existing contracts rather than the creation of new employment. The dynamics of employment at the regional level is characterized by a significant degree of heterogeneity. However, no specific regional patterns seems to emerge. The empirical analysis is based on data on the labor force (ISTAT) distinguished by regions and on administrative data (INPS) concerning the quantity, quality and duration of employment contracts.